The Formation of Vanadium Deposits in the Archean Rivière Bell Complex, Quebec: Insights from Fe-Ti Oxide Chemistry - Polivchuk, Matthew (Université d'Ottawa / University of Ottawa, 2018)
Cryptic trends in the trace element chemistry of Fe-Ti oxide minerals have been used to elucidate the magmatic processes responsible for the formation of Fe-Ti-V deposits in the Rivière Bell Complex layered mafic-ultramafic intrusion near Matagami, Quebec, Canada. Although metamorphism at greenschist-amphibolite facies conditions has modified the primary igneous compositions of magnetite and ilmenite, their Cr and V contents appear to have been unaffected. Chemostratigraphic variations of these elements in Fe-Ti oxides therefore remain valid tracers of magmatic differentiation, even in metamorphosed settings. Injections of compositionally evolved, Fe-Ti oxide-laden magma into a more primitive ferrogabbroic host are presumably responsible for sharp decreases in the Cr and V concentrations of Fe-Ti oxides that coincide with lithostratigraphic changes from predominantly disseminated gabbros to ultramafic sequences closely interlayered with massive oxides. These injections highlight the multistage magmatic history of the layered series of the Rivière Bell Complex and its vanadium ore horizons.
Keywords: layered intrusion; Fe-Ti-V deposits; Fe-Ti oxides; LA-ICP-MS; chemostratigraphy